The Effect of Foreign Direct Investment and Inflation on The Economic Growth of ASEAN Countries 2009-2020 - Ramadhanty, Firyal; Wasiaturrahma, Wasiaturrahma; Makatutu, Anas Iswanto Anwar (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2024)
This study aims to analyze the effect of foreign direct investment and inflation on economic growth in ASEAN countries. The analytical method used is a quantitative approach with multiple linear regression panel data method based on secondary data from foreign direct investment, inflation, and economic growth variables in 2009-2020. The analysis results show that FDI has no significant impact on the economic growth variable, and the inflation rate has a significant positive impact on the economic growth variable.